Genetics? no problem! - O'Dell, Kevin M. (Chichester, West Sussex ; Hoboken, NJ : John Wiley & Sons Inc., 2016)
"The analysis and interpretation of data is fundamental to the subject of genetics and forms a compulsory part of the undergraduate genetics curriculum. Indeed, the key skills that a genetics student requires are an ability to design and understand experimental strategies and to use problem-solving skills to interpret experimental results and data. Genetics? No Problem! provides students with a graded set of problems that aim to enthuse, challenge and entertain the reader. The book is divided into three sections - introductory; intermediate and advanced - each with 10 problems. For first level students there will be short genetics problems embedded in a wide range of scenarios, such as murder mysteries. As the book progresses, the stories will get longer and the science will get progressively more complex to challenge final year students and enable the reader to identify genetic disease in obscure organisms as well as designing and testing treatments and cures. Genetics? No Problem!: Takes a unique, innovative approach that provides students with a set of graded problems designed to develop both their skills, and their ability to tackle problems with confidence Includes problems embedded in a narrative, written in an interesting, informative and entertaining style by an Author with a proven track record in teaching, research and communication Is well illustrated in full colour throughout. The book will prove invaluable to all students of genetics across a range of disciplines needing to get to grips with the analysis and interpretation of data that is fundamental to the subject"--
"Takes a unique, innovative approach that provides students with a set of graded problems designed to develop both their skills, and their ability to tackle problems with confidence"--
Keywords: Genetics -- Vocational guidance; Genetics -- Miscellanea; SCIENCE / Life Sciences / Genetics & Genomics